2021
DOI: 10.1371/journal.pone.0248381
|View full text |Cite
|
Sign up to set email alerts
|

THz irradiation inhibits cell division by affecting actin dynamics

Abstract: Biological phenomena induced by terahertz (THz) irradiation are described in recent reports, but underlying mechanisms, structural and dynamical change of specific molecules are still unclear. In this paper, we performed time-lapse morphological analysis of human cells and found that THz irradiation halts cell division at cytokinesis. At the end of cytokinesis, the contractile ring, which consists of filamentous actin (F-actin), needs to disappear; however, it remained for 1 hour under THz irradiation. Inducti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…A conclusion was made, based on the changes in the intensity of the signal of a membrane-selective fluorescent dye FM4-64 upon the irradiation. Moreover, it was shown that the THz rays influenced F-actin polymerization both in vitro [ 24 ] and in vivo, in living cells [ 13 , 25 ]. Unfortunately, the effect described in viable cells was quite different—the destruction of actin filaments [ 25 ] and the induction of F-actin and its polarization [ 13 ] was observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A conclusion was made, based on the changes in the intensity of the signal of a membrane-selective fluorescent dye FM4-64 upon the irradiation. Moreover, it was shown that the THz rays influenced F-actin polymerization both in vitro [ 24 ] and in vivo, in living cells [ 13 , 25 ]. Unfortunately, the effect described in viable cells was quite different—the destruction of actin filaments [ 25 ] and the induction of F-actin and its polarization [ 13 ] was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that the THz rays influenced F-actin polymerization both in vitro [ 24 ] and in vivo, in living cells [ 13 , 25 ]. Unfortunately, the effect described in viable cells was quite different—the destruction of actin filaments [ 25 ] and the induction of F-actin and its polarization [ 13 ] was observed. Most likely, similar observations could be interpreted differently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For long-wavelength radiation, where the photon energy is far below that needed to induce chemical reactions (e.g., bond energies), and even below that of thermal photons at ambient temperature, one might wonder if any nonthermal mechanisms exist that can induce any biologically relevant changes. This question has been the topic of extensive studies for many years at lower frequencies and also, more recently, in the THz regime. In most of the cases when the data have been interpreted to show a nonthermal effect arising from exposure to THz light, the experiments did not employ the needed controls and statistics to rule out a more prosaic interpretation, such as heating. These are exceedingly challenging experiments, as (for example) it is almost impossible to rule out the possibility of spatially nonuniform transient heating with significant temperature variations on a subcellular length scale. Most notably, none of the purported nonthermal effects have ever been verified by a second independent research laboratory, and no plausible underlying mechanism has been proposed for how such effects could be induced by photons with only a few millivolts of energy.…”
Section: Introductionmentioning
confidence: 99%
“…Low-frequency THz radiation (0.46 THz) enhances the polymerization of purified actin in vitro, and by similarly affecting actin polymerization in vivo, inhibits human cell division. In an aqueous medium (~1 mm thick) at an irradiation frequency of 4 THz, both in vitro and in live cells, actin filaments disintegrated, possibly as the result of a shock wave [ 15 , 16 , 17 ]. The exposure of neuron-like PC 12 cells to THz radiation (0.3–19.5 THz) for 10 min temporarily increased the permeability of the cell membranes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%